1966
DOI: 10.1161/01.res.19.5.917
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Meters: Effects of Electrical Resistance in Tissues on Flow Measurements, and an Improved Calibration for Square-Wave Circuits

Abstract: Apparent sensitivity of magnetic meters applied to intact vessels can be altered by changes in conductivity of vessel walls or of the contained fluid, and by variable contact of the vessel with surrounding tissue or fluid. An experimental study of these problems was begun by designing a built-in magnetometer for complete electrical calibration of the square-wave meter. It was then found that flow of mercury, saline or blood of various hematocrits through nonconductive tubes gave signals equal to those calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1969
1969
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Generally there has been no distinction between the effect of hematocrit with and without a blood vessel present, and only rarely has the effect of fluid conductivity (as distinct from hematocrit) been examined or stated. The introduction of a blood vessel greatly alters the experimental conditions, and the way in which sensitivity depends upon hematocrit can be expected to vary with vessel geometry and conductivity (16,17). If, in the absence of a blood vessel, the instrument response is dependent upon fluid conductivity, as Beck et al (15) have shown the pulsedfield flowmeter to be, this effect and any due to hematocrit will be difficult to separate, …”
Section: Discussionmentioning
confidence: 99%
“…Generally there has been no distinction between the effect of hematocrit with and without a blood vessel present, and only rarely has the effect of fluid conductivity (as distinct from hematocrit) been examined or stated. The introduction of a blood vessel greatly alters the experimental conditions, and the way in which sensitivity depends upon hematocrit can be expected to vary with vessel geometry and conductivity (16,17). If, in the absence of a blood vessel, the instrument response is dependent upon fluid conductivity, as Beck et al (15) have shown the pulsedfield flowmeter to be, this effect and any due to hematocrit will be difficult to separate, …”
Section: Discussionmentioning
confidence: 99%
“…There is experimental evidence for vessel anisotropy with ur < ff8 <uF. Ferguson and Landahl (1966) observed 0 . 5 2 s ue/uFs 0.73 for the dog aorta, and Edgerton (1975) observed 0.25 S U , / U~~ 0.5 for the femoral, carotid, spleenic and renal arteries of the dog.…”
Section: Discussionmentioning
confidence: 94%
“…if vessel and blood are electrically indistinguishable), the sensitivity is also unaffected by the vessel size (Wyatt 1968). Measurements on freshly excised arteries have indicated that vessels have a lower conductivity than blood (see for example Ferguson and Landahl (1966) and Edgerton (1975), who have observed 0.25 C uW/uFC 0.73). Figure 2 depicts the sensitivity as a function of b / a for 0.25 S uW/uF C 1 , where S has been normalised to the value with no blood vessel present.…”
Section: Uniform Magnetic Fieldmentioning
confidence: 99%